ANGIOGENIC POTENTIAL OF THE HYDROXYAPATITE-BASED COMPOSITES LOADED WITH PLANT EXTRACT AND NANOPARTICLES - Holubnycha, Viktoriia; Govorun, Oleksandr; Pron, Veronika; Holubnycha, Marharyta; Yanovska, Ganna (Eastern Ukrainian Medical Journal, 2025)
Introduction. The growing ageing population and increasing incidence of bone-related disorders have intensified the demand for advanced regenerative materials. Hydroxyapatite-based composites enriched with metal nanoparticles and plant extracts show great promise due to their biocompatibility, antimicrobial activity, and ability to promote tissue regeneration. This study aimed to evaluate how such functionalized composites influence vessel formation using the chick chorioallantoic membrane (CAM) model. Methods. Hydroxyapatite-based composites were prepared by incorporating silver nanoparticles (10 µg/g) and pomegranate peel extract (30 mg/g) into hydroxyapatite, followed by stirring and drying. Supernatants of the obtained composites were applied onto the chick chorioallantoic membrane (CAM) of fertilized eggs on embryonic day 10 to assess angiogenic activity. After 24–48 h incubation, CAM images were taken and analyzed morphometrically using ImageJ to quantify vessel density and bifurcation points. Statistical significance was evaluated with GraphPad Prism (p < 0.05). The study was approved by the Local Ethical Committee (Decision No. 3/10, 16 October 2025). Results. Treatment with AgNPs loaded hydroxyapatite caused vessel dilation and tortuosity, whereas composites containing pomegranate extract—alone or combined with AgNPs—showed minimal vascular alterations. By day 12, a significant rise (p < 0.05) in vessel number was detected only in the group treated with composite containing pomegranate, highlighting its angiogenic activity, while the proportion of bifurcated vessels remained unchanged across all groups. Discussion. This study evaluated hydroxyapatite-based composites functionalized with silver nanoparticles (AgNPs) and pomegranate peel extract. Overall, the study demonstrates that the angiogenic response of hydroxyapatite-based composites depends on their functional components: silver nanoparticles suppress vessel formation, whereas pomegranate peel extract enhances it, highlighting the importance of composition in designing biomaterials for regenerative applications.